2015
DOI: 10.1038/cddis.2015.199
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 in the pathogenesis of ultraviolet-induced ocular surface inflammation

Abstract: High-mobility group box 1 (HMGB1) functions as a transcription-enhancing nuclear protein as well as a crucial cytokine that regulates inflammation. This study demonstrated that secretion of HMGB1 due to ultraviolet (UV) radiation inducing ocular surface inflammation-mediated reactive oxygen species (ROS) production. After treating conjunctival epithelial cells with UV radiation, HMGB1 was translocated from the nucleus to the cytoplasm and then eventually to the extracellular space. HMGB1 played a crucial role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Oxidation of HMGB1 attenuates its proinflammatory activity (55), particularly during apoptosis (56), when induction of immunological tolerance by apoptotic cells requires caspase-dependent oxidation of the protein (57) to eliminate danger signaling (58). UV exposure (which likely induces photo-oxidative damage by UV-induced ROS and not necrosis) seems to stimulate HMGB1 release by keratinocytes (59) or conjunctival epithelial cells as a stressorin (60). In addition, it was also reported that UV irradiation induces a TLR4/MYD88-driven neutrophilic skin inflammatory response in animal models initiated by HMGB1 release from damaged keratinocytes (61).…”
Section: Stressorins Respond To Stressmentioning
confidence: 99%
“…Oxidation of HMGB1 attenuates its proinflammatory activity (55), particularly during apoptosis (56), when induction of immunological tolerance by apoptotic cells requires caspase-dependent oxidation of the protein (57) to eliminate danger signaling (58). UV exposure (which likely induces photo-oxidative damage by UV-induced ROS and not necrosis) seems to stimulate HMGB1 release by keratinocytes (59) or conjunctival epithelial cells as a stressorin (60). In addition, it was also reported that UV irradiation induces a TLR4/MYD88-driven neutrophilic skin inflammatory response in animal models initiated by HMGB1 release from damaged keratinocytes (61).…”
Section: Stressorins Respond To Stressmentioning
confidence: 99%
“…1,2,9 In our previous study, we proved that reactive oxygen species (ROS) was important in translocation of HMGB1. 10 Hypoxia is defined as a low level of oxygen in the environment and oxygen concentrations of o5% are usually considered to be hypoxic. 11,12 In the nasal cavity, many pathologic diseases are related to tissue hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular HMGB1 binds to receptors for advanced glycation end products on cell surfaces to induce cellular signalling in inflammation, cell differentiation and cell migration . Many external stresses, which include reactive oxygen species (ROS) from ultraviolet (UV) irradiation and intracellular enzymatic reactions, are known to trigger release of HMGB1 from various cells, such as macrophages, monocytes and neutrophils . Release of HMGB1 from keratinocytes is similarly induced by UVB irradiation, potentially linking HMGB1 with certain pathological conditions of the skin …”
mentioning
confidence: 99%
“…15,16 Many external stresses, which include reactive oxygen species (ROS) from ultraviolet (UV) irradiation and intracellular enzymatic reactions, are known to trigger release of HMGB1 from various cells, such as macrophages, monocytes and neutrophils. [17][18][19][20] Release of HMGB1 from keratinocytes is similarly induced by UVB irradiation, potentially linking HMGB1 with certain pathological conditions of the skin. 21 Released HMGB1 may act as a damage-associated molecular pattern (DAMP) molecule, inducing immune responses through proinflammatory molecular production.…”
mentioning
confidence: 99%